Propellanes as Rigid Scaffolds for the Stereodefined Attachment of σ-Pharmacophoric Structural Elements to Achieve σ Affinity - Torres-Gómez, Héctor (Int J Mol Sci, 2021)
Following the concept of conformationally restriction of ligands to achieve high receptor affinity, we exploited the propellane system as rigid scaffold allowing the stereodefined attachment of various substituents. Three types of ligands were designed, synthesized and pharmacologically evaluated as σ(1) receptor ligands. Propellanes with (1) a 2-methoxy-5-methylphenylcarbamate group at the “left” five-membered ring and various amino groups on the “right” side; (2) benzylamino or analogous amino moieties on the “right” side and various substituents at the left five-membered ring and (3) various urea derivatives at one five-membered ring were investigated. The benzylamino substituted carbamate syn,syn-4a showed the highest σ(1) affinity within the group of four stereoisomers emphasizing the importance of the stereochemistry. The cyclohexylmethylamine 18 without further substituents at the propellane scaffold revealed unexpectedly high σ(1) affinity (K(i) = 34 nM) confirming the relevance of the bioisosteric replacement of the benzylamino moiety by the cyclohexylmethylamino moiety. Reduction of the distance between the basic amino moiety and the “left” hydrophobic region by incorporation of the amino moiety into the propellane scaffold resulted in azapropellanes with particular high σ(1) affinity. As shown for the propellanamine 18, removal of the carbamate moiety increased the σ(1) affinity of 9a (K(i) = 17 nM) considerably. Replacement of the basic amino moiety by H-bond forming urea did not lead to potent σ ligands. According to molecular dynamics simulations, both azapropellanes anti-5 and 9a as well as propellane 18 adopt binding poses at the σ(1) receptor, which result in energetic values correlating well with their different σ(1) affinities. The affinity of the ligands is enthalpy driven. The additional interactions of the carbamate moiety of anti-5 with the σ(1) receptor protein cannot compensate the suboptimal orientations of the rigid propellane and its N-benzyl moiety within the σ(1) receptor-binding pocket, which explains the higher σ(1) affinity of the unsubstituted azapropellane 9a.